IDENTIFICATION AND ANTIMICROBIAL ACTIVITY OF ACTINOMYCETES STRAINS ISOLATED FROM SAMPLES COLLECTED IN THE COASTAL AREA OF HUE, DA NANG AND QUANG NAM PROVINCES, VIETNAM - Tuan, Cao Duc; Hong Minh, Le Thi; Quyen, Vu Thi; Anh, Nguyen Mai; Mai Huong, Doan Thi; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Biotechnology, 2018)
Microorganisms are of particular interest because of their ability to synthesize high-value secondary compounds and provide us with novel and diverse chemical structures. The most common source of antibiotics is Actinomycetes which provide around two-third of naturally occurring antibiotics, including many of medical importance. In this study, 81 strains of actinomycetes were isolated from 145 samples including: sediments, sponges, soft corals, echinoderms and starfish collected from three sea areas of Vietnam: Hue, Da Nang and Quang Nam. The strains were fermented in A+ medium and fermentation broths were extracted 5 times with ethyl acetate. The extracts were evaporated under reduced pressure to yield crude extracts. Quantitative assay was used to determine MIC (Minimum inhibitory concentration) of extract against 7 reference strains. From the results of screening, Seven strains of actinomycetes that have the highest biological activity (Code: G244, G246, G261, G266, G278, G280 and G290) were chosen to be identified by morphological and phylogenetic based on 16S rRNA gene sequences. The results showed that 6 strains G246, G261, G266, G278, G280 and G290 belonged to the genus Streptomyces; and the strain G244 belonged to the genus Micromonospora. In particular, strains G244, G278, G280 were resistant 5/7 strains of microorganisms test, with values MICs from 2 µg/mL to 256 µg/mL; and three strains G261, G266, G290 showed the inhibitory effect towards 4/7 strains of microorganisms test, with respective values MICs from 2 µg/mL to 256 µg/mL. Moreover, six of the seven selected strains were highly resistant to yeast Candida albicans ATCC10231 with MIC values from 2 µg/mL to 256 µg/mL. These results indicated that marine Actinomycetes in Vietnam are also a potential source to find bioactive substances.